THE ROLE OF METABOLIC DISORDERS IN THE PATHOGENESIS AND PROGRESSION OF CHRONIC TUBULOINTERSTITIAL NEPHRITIS IN CHILDREN (LITERATURE REVIEW) - Akhmatova Yulduz Ablakulovna,; Alkov Ruslan Alimjonovich,; Lutfullaev Khafizullo Zaynullaevich, (World Scientific Research Journal, 2025)
Chronic tubulointerstitial nephritis (CTIN) represents a major contributor to chronic kidney disease (CKD) in the pediatric population, where metabolic disorders increasingly emerge as pivotal pathogenic drivers. This review synthesizes current evidence linking dysmetabolic states—such as hyperuricemia, dyslipidemia, obesity, and insulin resistance—to tubulointerstitial injury and fibrosis in children. Persistent metabolic imbalance triggers oxidative stress, inflammasome activation, and immune dysregulation, initiating a self-perpetuating cycle of inflammation, hypoxia, and extracellular matrix expansion. Crystalline nephropathies caused by urate and oxalate deposition act as potent inducers of the NLRP3 inflammasome, while metabolic syndrome components amplify renal oxidative stress and endothelial dysfunction. Early-life exposure to metabolic stressors further predisposes to structural and functional renal impairment. Despite growing recognition of these mechanisms, pediatric-specific data remain limited, emphasizing the need for early detection of metabolic risk and biomarker-guided preventive interventions. Targeted management of dysmetabolism—including dietary regulation, antioxidant therapy, and metabolic correction—offers promising strategies to halt CTIN progression and preserve renal function in children.